Total phenolic content and primary antioxidant activity of methanolic and ethanolic extracts of aromatic plants’ leaves - A. A., Azlim Almey; C., Ahmed Jalal Khan; I., Syed Zahir; K., Mustapha Suleiman; M. R., Aisyah; K., Kamarul Rahim (Universiti Putra Malaysia, 2010)
The aim of this study is to determine the total phenolic content and primary antioxidant activity of methanolic and ethanolic extracts of four aromatic plants’ leaves namely knotweed (Polygonum minus), curry (Murraya koenigii), kaffir lime (Citrus hysrix) and fragrant screwpine (Pandanus odurus). Total phenolic content (TPC) assay using Folin-Ciocalteu method was used to assess the presence and level of phenolic compounds in each sample. The present study showed that both methanolic and ethanolic extracts of P. minus had the highest TPC and followed by M. koenigii, C. hystrix and P. odorus. Primary antioxidant activity in terms of free radical scavenging activities of both methanolic and ethanolic extracts was then measured by 2, 2, diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity assay. The lowest EC50 values based on the DPPH. radical scavenging activity were shown by P. minus extracts as compared to the other samples. For both ethanolic and methanolic extracts, the correlations between TPC and EC50 based on the DPPH. radical scavenging activity assay were negative and weak. Relatively, the present results suggest that of the four aromatic plants, P. minus and M. koenigii have shown potential as sources of natural antioxidants.